Revisiting reflexive archaeology at Çatalhöyük: integrating digital and 3D technologies at the trowel's edge. (8th April 2015) - Berggren, Åsa; Dell'Unto, Nicolo; Forte, Maurizio; Haddow, Scott; Hodder, Ian; Issavi, Justine; Lercari, Nicola; Mazzucato, Camilla; Mickel, Allison; Taylor, James S.
Abstract